Promoting differentiation of human-induced pluripotent stem cells into sinoatrial node-like cells through programmed regulation of AMPK signalling pathway - Liu, Feng; Xue, Zongqian; Lan, Huan; Wan, Juyi; Yang, Chenyu; Cyganek, Lukas; Hamdani, Nazha; Yu, Fengxu; Liao, Bin; Zhou, Xiao-Bo; El-Battrawy, Ibrahim; Akın, Ibrahim (Europace, 2025)
The differentiation of human-induced pluripotent stem cells (hiPSCs) into sinoatrial node (SAN)-like cells (SANLCs) remains challenged by complex differentiation protocols and low efficiency. This study aims to reveal the role of AMPK signalling in the differentiation process of hiPSCs into SANLCs, providing new strategies for obtaining SANLCs in vitro.Cells from the cardiac mesodermal stage, cardiac progenitor cell stage, and cardiomyocyte stage during differentiation of hiPSCs to cardiomyocytes (hiPSC-CMs) were taken for transcriptome sequencing and analyses. PCR, immunostaining, western blot, FACS, and patch-clamp techniques were employed for the analyses of differentiated hiPSC-CMs. Kyoto Encyclopedia of Genes and Genomes analysis identified that the AMPK signalling pathway is significantly enriched with the expression of NKX2.5 (sinus node cell development-related transcription factor). The early activation and late inhibition of AMPK signalling were both effective in the up-regulation of SANLC markers. In addition, the combined manipulation of both stages further enhanced the differentiation efficiency reflected by higher SANLC marker expression, which was also confirmed at the protein level by immunofluorescence, western blot, and flow cytometry analyses. SANLCs obtained from the differentiation with combined modulation of AMPK signalling displayed typical features of native pacemaker cells in the heart, including ion channel currents (IKAch, ICaT, ICaL, If), action potentials, and robust autonomic responsiveness to both β-adrenergic and muscarinic stimulation.Early activation and then inhibition of the AMPK signalling pathway during the differentiation process can promote hiPSC differentiation to SANLCs, which may provide a novel strategy for obtaining SANLCs for studies on SAN diseases.
Online veröffentlicht: 6. November 2025
Gesehen am 27.01.2026